Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

Phenolized lignin binders inducing ultrathin SEI of hard carbon for advanced sodium storage - Jinxing Li; Zhipeng Qiu; Fangbao Fu; Weifeng Liu; Jianbin Mo; Dongjie Yang; Xueqing Qiu (Chemical Engineering Journal, 2026)

Detection, isolation and molecular characterization of Senecavirus A in porcine semen: Implications for control programs - Xiaozhan Zhang; Xiuqing Li; Yiwen Liu; Nannan Lv; Beibei Yang; Shihao Fu; Zenghai Jiang; Pandeng Zhao; Yunze Guo; Jinxing Song; Chuanzhou Bian; Decheng Yang; et al. (The Veterinary Journal, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Design, synthesis and antitumour activity of pyrimidine derivatives as novel selective EGFR kinase inhibitors - Cheng Zhang; Yiwen Huo; Jianfang Fu; Yue Liu; Qinjiang Zhou; Mingyue Hou; Xiaoxuan Duan; Yanna Lv; Jinxing Hu (Molecular Diversity, 2025)

Tea polyphenols attenuate glufosinate-induced breast injury by reducing endoplasmic reticulum stress and autophagy - Fu Li; Zhanhang Wang; Muhua Luo; Jiaxiang Hu; Haifeng Wang; Yonglong He; Danni Li; Yuan Yuan; Jinxing Hou; Yuxuan Song; Lei Zhang; Binyun Cao; et al. (Journal of Hazardous Materials, 2025)

Cytological and genetic analyses of the seed number per silique locus BnSNSC09 in Brassica napus - Wenhao Shen; Tanglingdian He; Jinxiang Gao; Pei Qin; Kaining Hu; Jing Wen; Bin Yi; Chaozhi Ma; Jinxiong Shen; Tingdong Fu; Jinxing Tu (Theoretical and Applied Genetics, 2025)

Diversity of biological activities of crude venom extracted from five species of South China Sea anemones - Panmin He; Ming Li; Jinxing Fu; Yanling Liao; Bo Yi; Bingmiao Gao (Frontiers in Marine Science, 2024)
Developing novel, efficient, and safe peptide drugs from sea anemones has aroused great interest in countries around the world today. Sea anemones contain complex protein and peptide toxins, which determine the diversity of their biological activities. In this study, a variety of activities were assessed for crude venom extracted from five species of South China Sea anemones, including hemolytic, enzyme inhibition, anticancer, insecticidal, analgesic and lethal activities. The most toxic sea anemone was found to be Heteractis magnifica , which has high lethal activity in mice with an LD 50 of 11.0 mg/kg. The crude venom of H. magnifica also exhibited a range of the most potent activities, including hemolytic, trypsin inhibitory, cytotoxic activity against U251 and A549 cells, insecticidal and analgesic activities. In addition, the crude venom of Stichodactyla haddoni was the most effective inhibitor of pepsin, and the crude venom of Heteractis crispa was extremely strong toxicity to HepG2 cells. These findings are of great significance for exploring the potential and application of South China Sea anemone resources, and are expected to provide new directions and possibilities for the development of novel anticancer drugs, analgesics and biopesticides.

Developmental pleiotropy of SDP1 from seedling to mature stages in B. napus - Baolong Tao; Yina Ma; Liqin Wang; Chao He; Junlin Chen; Xiaoyu Ge; Lun Zhao; Jing Wen; Bin Yi; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Plant Molecular Biology, 2024)

Oxidation of amine-based pharmaceuticals with unactivated peroxymonosulfate: Kinetics, mechanisms, and elimination efficiency of NDMA formation - Yang Zhou; Junhao Fu; Zhu Zeng; Yuan Gao; Zhong Zhang; Bin Han; Jinxing Ma; Jin Jiang (Journal of Hazardous Materials, 2024)

Fine mapping of BnDM1—the gene regulating indeterminate inflorescence in Brassica napus - Jiao Chen; Sihao Zhang; Bao Li; Chenjian Zhuo; Kaining Hu; Jing Wen; Bin Yi; Chaozhi Ma; Jinxiong Shen; Tingdong Fu; Jinxing Tu (Theoretical and Applied Genetics, 2023)

miR319 and its target TCP4 involved in plant architecture regulation in Brassica napus - Hongchen Lu; Li Chen; Mengjie Du; Haiqin Lu; Jie Liu; Shenhua Ye; Baolong Tao; Rihui Li; Lun Zhao; Jing Wen; Bin Yi; Jinxing Tu; et al. (Plant Science, 2023)

High conopeptide diversity in Conus striatus: Revealed by integration of two transcriptome sequencing platforms - Yanling Liao; Chao Peng; Yabing Zhu; Jinxing Fu; Zhiqiang Ruan; Qiong Shi; Bingmiao Gao (Frontiers in Marine Science, 2022)
Marine cone snail venoms represent a vast library of bioactive peptides with proven potential as research tools, drug leads, and therapeutics. In this study, a transcriptome library of four different organs, namely radular sheath, venom duct, venom gland, and salivary gland, from piscivorous Conus striatus was constructed and sequenced using both Illumina next-generation sequencing (NGS) and PacBio third-generation sequencing (TGS) technologies. A total of 428 conotoxin precursor peptides were retrieved from these transcriptome data, of which 413 conotoxin sequences assigned to 13 gene superfamilies, and 15 conotoxin sequences were classified as unassigned families. It is worth noting that there were significant differences in the diversity of conotoxins identified from the NGS and TGS data: 82 conotoxins were identified from the NGS datasets while 366 conotoxins from the TGS datasets. Interestingly, we found point mutations in the signal peptide sequences of some conotoxins with the same mature sequence. Therefore, TGS broke the traditional view of the conservation of conotoxin signal peptides and the variability of mature peptides obtained by NGS technology. These results shed light on the integrated NGS and TGS technologies to mine diverse conotoxins in Conus species, which will greatly contribute to the discovery of novel conotoxins and the development of new marine drugs.

Transcriptome Sequencing of the Pale Anemones (Exaiptasia diaphana) Revealed Functional Peptide Gene Resources of Sea Anemone - Jinxing Fu; Yanbin He; Chao Peng; Tianle Tang; Aihua Jin; Yanling Liao; Qiong Shi; Bingmiao Gao (Frontiers in Marine Science, 2022)
Sea anemone venom is a marine drug resource library with pharmacological and biotechnology value, and it contains complex and diverse functional peptide neurotoxins. However, the venom components of only a limited number of sea anemone species have been globally evaluated by transcriptomics and proteomics. In this study, 533 putative protein as well as peptide toxin sequences were found on a large scale from dissimilar developmental stages of sea anemone Exaiptasia diaphana , which can be divided into 75 known superfamilies according to the predicted functions. Among them, the proportion of protein is 72.98%, and its main families are metalloproteases, chymotrypsinogen like, collagen, pancreatic lipase-associated protein like, and G-protein coupled receptor, while the proportion of peptides is 27.02%, and main families are ShK domain, thrombin, Kunitz-type, defensin, as well as insulin-like peptide. Finally, typical anemone peptide neurotoxins were screened, and the 3D structure and pharmacological activity of these anemone peptide neurotoxins were predicted by homology modeling. We elucidate on a valuable high-throughput approach for obtaining sea anemone proteins and peptides. Our findings form the basis for targeted studies on the diversity as well as pharmacological effects of sea anemone peptide neurotoxins.

BnA1.CER4 and BnC1.CER4 are redundantly involved in branched primary alcohols in the cuticle wax of Brassica napus - Jie Liu; Lixia Zhu; Benqi Wang; Huadong Wang; Imran khan; Shuqin Zhang; Jing Wen; Chaozhi Ma; Cheng Dai; Jinxing Tu; Jinxiong Shen; Bin Yi; et al. (Theoretical and Applied Genetics, 2021)

A mitochondria-localized pentatricopeptide repeat protein is required to restore hau cytoplasmic male sterility in Brassica napus - Huadong Wang; Qing Xiao; Chao Wei; Hui Chen; Xiaohan Chen; Cheng Dai; Jing Wen; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen; Bin Yi (Theoretical and Applied Genetics, 2021)

Erratum to: Label‑Free Quantitative Proteomic Profiling Identifies Potential Active Components to Exert Pharmacological Effects in the Fruit of Alpinia oxyphylla by Mass Spectrometry - Yakun Dai; Lin Yuan; Jinxing Fu; Bingmiao Gao (Journal of Plant Biology, 2021)

Label-Free Quantitative Proteomic Profiling Identifies Potential Active Components to Exert Pharmacological Effects in the Fruit of Alpinia oxyphylla by Mass Spectrometry - Yakun Dai; Lin Yuan; Jinxing Fu; Bingmiao Gao (Journal of Plant Biology, 2020)

Disruption of carotene biosynthesis leads to abnormal plastids and variegated leaves in Brassica napus - Xiaobin Zhao; Kaining Hu; Mengjiao Yan; Bin Yi; Jing Wen; Chaozhi Ma; Jinxiong Shen; Tingdong Fu; Jinxing Tu (Molecular Genetics and Genomics, 2020)
Leaf color is an important characteristic of normal chloroplast development. Variegated plants have green- and white-sectored leaves, which can be used to identify important pathways and molecular mechanisms of chloroplast development. We studied two Brassica napus variegation mutants from same one variegated ancestor, designated ZY-4 and ZY-8, which have different degrees of variegation. When grown in identical conditions, the ratio of white sectors in ZY-4 leaves is higher than in ZY-8. In both mutants, the cells in green sectors contain normal chloroplasts; while, the cells in white sectors contain abnormal plastids. Seedling chloroplasts ultrastructure of both mutants showed that the biogenesis of chloroplasts was blocked in early stages; delayed development and structual damage in ZY-4 were more serious than in ZY-8. Employing bulked segregant analysis(BSA), two bulks (BY142 and BY137) from BC 2 F 1 lines derived from ZY-4 and ZS11, and one bulk (BY56) from BC 2 F 1 lines derived from ZY-8 and ZS11, and screening by Brassica 60K SNP BeadChip Array, showed the candidate regions localized in chromosome A08 (BY142), C04 (BY137), and A08 (BY56), respectively. Transcriptome analysis of five seedling development stages of ZY-4, ZY-8, and ZS11 showed that photosynthesis, energy metabolism-related pathways and translation-related pathways were important for chloroplast biogenesis. The number of down- or up-regulated genes related to immune system process in ZY-4 was more than in ZY-8. The retrograde signaling pathway was mis-regulated in both mutants. DEG analysis indicated that both mutants showed photooxidative damages. By coupling transcriptome and BSA CHIP analyses, some candidate genes were identified. The gene expression pattern of carotene biosynthesis pathway was disrupted in both mutants. However, histochemical analysis of ROS revealed that there was no excessive accumulation of ROS in ZY-4 and ZY-8. Taken together, our data indicate that the disruption of carotene biosynthetic pathways leads to the variegation phenotypes of ZY-4 and ZY-8 and there are some functions that can compensate for the disruption of carotene biosynthesis in ZY-4 and ZY-8 to reduce ROS and prevent seedling mortality.

Transcriptome profiling reveals cytokinin promoted callus regeneration in Brassica juncea - Hongchen Lu; Ping Xu; Kaining Hu; Qing Xiao; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Identification and fine mapping of a major locus controlling branching in Brassica napus - Bao Li; Jinxiang Gao; Jiao Chen; Zhixin Wang; Wenhao Shen; Bin Yi; Jing Wen; Chaozhi Ma; Jinxiong Shen; Tingdong Fu; Jinxing Tu (Theoretical and Applied Genetics, 2020)

Fine mapping of a silique length- and seed weight-related gene in Brassica napus - Wenhao Shen; Pei Qin; Mengjiao Yan; Bao Li; Zengxiang Wu; Jing Wen; Bin Yi; Chaozhi Ma; Jinxiong Shen; Tingdong Fu; Jinxing Tu (Theoretical and Applied Genetics, 2019)

High-throughput identification of SNPs reveals extensive heterosis with intra-group hybridization and genetic characteristics in a large rapeseed (Brassica napus L.) panel - Xiang Luo; Yongqiang Tan; Chaozhi Ma; Jinxing Tu; Jinxiong Shen; Bin Yi; Tingdong Fu (Euphytica, 2019)

Construction of restorer lines and molecular mapping for restorer gene of hau cytoplasmic male sterility in Brassica napus - Chao Wei; Huadong Wang; Shuangping Heng; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Jinxiong Shen; Tingdong Fu (Theoretical and Applied Genetics, 2019)

Association mapping of salt tolerance traits at germination stage of rapeseed (Brassica napus L.) - Heping Wan; Yinke Wei; Jiali Qian; Yunlei Gao; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Euphytica, 2018)

Identification of different cytoplasms based on newly developed mitotype-specific markers for marker-assisted selection breeding in Brassica napus L. - Shuangping Heng; Fengyi Chen; Chao Wei; Kaining Hu; Zonghui Yang; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Ping Si; Tingdong Fu; Jinxiong Shen (Plant Cell Reports, 2017)

Heme oxygenase 1 defects lead to reduced chlorophyll in Brassica napus - Lixia Zhu; Zonghui Yang; Xinhua Zeng; Jie Gao; Jie Liu; Bin Yi; Chaozhi Ma; Jinxiong Shen; Jinxing Tu; Tingdong Fu; Jing Wen (Plant Molecular Biology, 2017)

Fine mapping and candidate gene analysis of an anthocyanin-rich gene, BnaA.PL1, conferring purple leaves in Brassica napus L. - Haibo Li; Lixia Zhu; Gaigai Yuan; Shuangping Heng; Bin Yi; Chaozhi Ma; Jinxiong Shen; Jinxing Tu; Tingdong Fu; Jing Wen (Molecular Genetics and Genomics, 2016)

Dynamic transcriptome analysis reveals AP2/ERF transcription factors responsible for cold stress in rapeseed (Brassica napus L.) - Chunfang Du; Kaining Hu; Shuanshi Xian; Chunqing Liu; Jianchun Fan; Jinxing Tu; Tingdong Fu (Molecular Genetics and Genomics, 2016)

Genetic distance revealed by genomic single nucleotide polymorphisms and their relationships with harvest index heterotic traits in rapeseed (Brassica napus L.) - Xiang Luo; Chaozhi Ma; Bin Yi; Jinxing Tu; Jinxiong Shen; Tingdong Fu (Euphytica, 2016)

Mapping of QTL associated with waterlogging tolerance and drought resistance during the seedling stage in oilseed rape (Brassica napus) - Zhen Li; Shufang Mei; Zhong Mei; Xianglei Liu; Tingdong Fu; Guangsheng Zhou; Jinxing Tu (Euphytica, 2014)

Comparative mapping reveals similar linkage of functional genes to QTL of yield-related traits between Brassica napus and Oryza sativa - FUPENG LI; CHAOZHI MA; QINGFANG CHEN; TOUMING LIU; JINXIONG SHEN; JINXING TU; YONGZHONG XING; TINGDONG FU (Journal of Genetics, 2012)

Characterization of interploid hybrids from crosses between Brassica juncea and B. oleracea and the production of yellow-seeded B. napus - Jing Wen; Lixia Zhu; Liping Qi; Hongmei Ke; Bin Yi; Jinxiong Shen; Jinxing Tu; Chaozhi Ma; TingDong Fu (Theoretical and Applied Genetics, 2012)

Mapping of BnMs4 and BnRf to a common microsyntenic region of Arabidopsis thaliana chromosome 3 using intron polymorphism markers - Shengqian Xia; Ling Cheng; Feng Zu; Xiaoling Dun; Zhengfu Zhou; Bin Yi; Jing Wen; Chaozhi Ma; Jinxiong Shen; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2012)

Identification, fine mapping and characterisation of a dwarf mutant (bnaC.dwf) in Brassica napus - Xinhua Zeng; Lixia Zhu; Yanli Chen; Liping Qi; Yuanyuan Pu; Jing Wen; Bin Yi; Jinxiong Shen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2011)

Mapping of QTLs detected in a Brassica napus DH population for resistance to Sclerotinia sclerotiorum in multiple environments - Xiangrui Yin; Bin Yi; Wei Chen; Weijie Zhang; Jinxing Tu; W. G. Dilantha Fernando; Tingdong Fu (Euphytica, 2010)

Effects of Bleomycin on microspore embryogenesis in Brassica napus and detection of somaclonal variation using AFLP molecular markers - Xinhua Zeng; Jing Wen; Zhengjie Wan; Bin Yi; Jinxiong Shen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Broadening the avenue of intersubgenomic heterosis in oilseed Brassica - Jun Zou; Jiali Zhu; Shunmou Huang; Entang Tian; Yong Xiao; Donghui Fu; Jinxing Tu; Tingdong Fu; Jinling Meng (Theoretical and Applied Genetics, 2010)

A separation defect of tapetum cells and microspore mother cells results in male sterility in Brassica napus: the role of abscisic acid in early anther development - Yun Zhu; Xiaoling Dun; Zhengfu Zhou; Shengqian Xia; Bin Yi; Jing Wen; Jinxiong Shen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Plant Molecular Biology, 2010)

The inheritance of seed color in a resynthesizedBrassica napus line No. 2127-17 including a new epistatic locus - Yan Zhang; Xia Li; Chaozhi Ma; Jinxiong Shen; Baoyuan Chen; Jinxing Tu; Tingdong Fu (Genes & Genomics, 2009)

Analysis of gene expression profile in pollen development of recessive genic male sterile Brassica napus L. line S45A - Yuning Chen; Shaolin Lei; Zhengfu Zhou; Fangqin Zeng; Bin Yi; Jing Wen; Jinxiong Shen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Plant Cell Reports, 2009)

Identification of AFLP and SCAR markers linked to the male fertility restorer gene of pol CMS (Brassica napus L.) - Fangqin Zeng; Bin Yi; Jinxing Tu; Tingdong Fu (Euphytica, 2009)

Molecular markers linked to Bn;rf: a recessive epistatic inhibitor gene of recessive genic male sterility in Brassica napus L. - Lu Xiao; Bin Yi; Yufeng Chen; Zhen Huang; Wei Chen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Euphytica, 2008)

Distribution of S haplotypes and its relationship with restorer–maintainers of self-incompatibility in cultivated Brassica napus - Xingguo Zhang; Chaozhi Ma; Jiayou Tang; Wei Tang; Jinxing Tu; Jinxiong Shen; Tingdong Fu (Theoretical and Applied Genetics, 2008)

Genetic characterization of a new cytoplasmic male sterility system (hau) in Brassica juncea and its transfer to B. napus - Zhengjie Wan; Bing Jing; Jinxing Tu; Caozhi Ma; Jinxiong Shen; Bin Yi; Jing Wen; Tao Huang; Xianjun Wang; Tingdong Fu (Theoretical and Applied Genetics, 2008)

Detection of QTL for six yield-related traits in oilseed rape (Brassica napus) using DH and immortalized F2 populations - Wei Chen; Yan Zhang; Xueping Liu; Baoyuan Chen; Jinxing Tu; Fu Tingdong (Theoretical and Applied Genetics, 2007)

Towards map-based cloning: fine mapping of a recessive genic male-sterile gene (BnMs2) in Brassica napus L. and syntenic region identification based on the Arabidopsis thaliana genome sequences - Shaolin Lei; Xueqin Yao; Bin Yi; Wei Chen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2007)

Fine mapping of the recessive genic male sterility gene (Bnms3) in Brassica napus L. - Zhen Huang; Yufeng Chen; Bin Yi; Lu Xiao; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2007)

Fine mapping of the recessive genic male-sterile gene (Bnms1) in Brassica napus L. - Bin Yi; Yuning Chen; Shaolin Lei; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2006)

Development of SCAR and CAPS Markers for a Partially Dominant Yellow Seed Coat Gene in Brassica Napus L - Zhiwen Liu; Tingdong Fu; Ying Wang; Jinxing Tu; Baoyuan Chen; Yongming Zhou; Chaozhi Ma; Lianmin Shan (Euphytica, 2006)